Technical and Relational Drivers of Loyalty and Switching Intention among B2B Customers - Irfan Chairudin; Ahmad Ikhwan Setiawan (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: The automotive refinishing industry is an important part of the automotive aftermarket ecosystem that relies on long-term relationships between suppliers and business-to-business (B2B) customers. In an increasingly competitive environment, understanding the factors influencing customer satisfaction, customer loyalty, and switching intention is essential to support business sustainability. Objective: This study aims to examine the effects of product quality, technical service quality, brand image, relationship marketing, and product availability on customer satisfaction, customer loyalty, and switching intention, as well as to investigate the moderating role of perceived switching cost. Methods: This study employed a quantitative explanatory approach involving 196 B2B customers in the automotive refinishing industry in Indonesia. Data were collected through a structured questionnaire survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The findings indicate that product quality, technical service quality, brand image, relationship marketing, and product availability positively affect customer satisfaction. Relationship marketing and product availability also have positive effects on customer loyalty. Customer satisfaction significantly increases customer loyalty and reduces switching intention, while customer loyalty negatively affects switching intention. Furthermore, perceived switching cost strengthens the effects of customer satisfaction and customer loyalty in reducing switching intention. Conclusion: Customer loyalty in the automotive refinishing industry is influenced by a combination of technical and relational factors. Companies should enhance product quality, technical services, product availability, brand image, and customer relationships to improve customer satisfaction and loyalty while reducing customers’ propensity to switch to alternative suppliers.